Concepts and definitions of healthy ageing: a systematic review and synthesis of theoretical models. (February 2023) - Menassa, Marilyne; Stronks, Karien; Khatmi, Farnaz; Roa Díaz, Zayne Milena; Espinola, Octavio Pano; Gamba, Magda; Itodo, Oche Adam; Buttia, Chepkoech; Wehrli, Faina; Minder, Beatrice; Velarde, Minerva Rivas; Franco, Oscar H.
Summary: Background: Healthy ageing (HA) has been defined using multiple approaches. We aim to produce a comprehensive overview and analysis of the theoretical models underpinning this concept and its associated normative terms and definitions. Methods: We conducted a systematic review of peer-reviewed HA models in Embase.com, Medline (Ovid), Cochrane CENTRAL, CINAHL, PsycINFO, and Web of Science until August 2022. Original theoretical papers, concept analyses, and reviews that proposed new models were included. Operational models/definitions, development psychology theories and mechanisms of ageing were excluded. We followed an iterative approach to extract the models' characteristics and thematically analyze them based on the approach of Walker and Avant. The protocol was registered in PROSPERO (CRD42021238796). Findings: Out of 10, 741 records, we included 59 papers comprising 65 models/definitions, published in English (1960–2022) from 16 countries in Europe, Asia, and America. Human ageing was described using 12 normative terms, mainly (models (%)): successful (34 (52%)), healthy (eight (12%)), well (five (8%)), and active (four (6%)). We identified intrinsic/extrinsic factors interacting throughout the life course, adaptive processes as attributes, and outcomes describing ageing patterns across objective and subjective dimensions (number of models/definitions): cognitive (62), psychological (53), physical (49), social (49), environmental (19), spiritual (16), economic (13), cultural (eight), political (six), and demographic (four) dimensions. Three types of models emerged: health-state outcomes (three), adaptations across the life course (31), or a combination of both (31). Two additional sub-classifications emphasized person-environment congruence and health promotion. Interpretation: HA conceptualizations highlight its multidimensionality and complexity that renders a monistic model/definition challenging. It has become evident that life long person-environment interactions, adaptations, environments, and health promotion/empowerment are essential for HA. Our model classification provides a basis for harmonizing terms and dimensions that can guide research and comparisons of empirical findings, and inform social and health policies enabling HA for various populations and contexts. Funding: MM, ZMRD, and OI are supported by the European Union's Horizon 2020 Marie Skłodowska-Curie grant No 801076, and MM is also supported by the Swiss National Foundation grant No 189235 .